Exploring the Burden Behind the Mask of Siboan Goar's Identity in Batak Toba Culture: A Case Study - Lydia Putri Angela Sitorus; Chamilul Hikam Al Karim (Psikostudia : Jurnal Psikologi, 2026)
Siboan Goar, the firstborn son in a Batak Toba family, carries significant cultural expectations as the successor to the family name and clan, potentially triggering psychological distress. This qualitative case study explores the identity and role dynamics associated with this position. Using purposive sampling, the study included three Siboan Goar as primary participants, three parents of Siboan Goar, and two traditional leaders as supporting participants. Data were collected through semi-structured interviews and analyzed using reflective thematic analysis with the assistance of NVivo 12 Plus. The results identified seven overarching themes: internal factors, external factors, expectations, marriage, impacts, coping mechanisms, and cultural reflections. The findings showed that cultural pressure can cause psychological and physical distress, which is more pronounced after marriage. To cope with these pressures, participants employed both problem-focused and emotion-focused coping strategies. The study also reveals a gradual deconstruction of male primacy toward gender equality through cultural reflection, encouraging awareness and change. Ultimately, this study advances the understanding of culture-based mental health issues in Indonesia.Siboan Goar atau anak laki-laki pertama dalam keluarga Batak Toba mengemban ekspektasi kultural besar sebagai penerus nama dan marga yang rentan memicu tekanan psikologis. Penelitian kualitatif studi kasus ini mengeksplorasi identitas dan dinamika peran tersebut. Melalui purposive sampling, penelitian ini melibatkan 3 Siboan Goar sebagai partisipan utama, serta 3 orang tua Siboan Goar dan 2 tokoh adat sebagai partisipan pendukung. Data dikumpulkan melalui wawancara semi-terstruktur, lalu dianalisis menggunakan metode analisis tematik reflektif dengan bantuan software NVIVO 12 Plus. Hasilnya mengidentifikasi 7 tema final, yaitu faktor internal, faktor eksternal, harapan, pernikahan, dampak, mekanisme koping, dan refleksi budaya. Temuan penelitian ini menunjukkan bahwa tekanan kultural dapat memicu dampak psikologis maupun fisik yang semakin menguat pasca-pernikahan. Guna bertahan, individu menerapkan problem-focused coping dan emotion-focused coping. Penelitian ini juga mengungkap adanya dekonstruksi male primacy menuju kesetaraan gender melalui refleksi budaya. Implikasinya, penelitian ini memperkaya literatur kesehatan mental berbasis budaya di Indonesia guna mencegah normalisasi beban psikologis adat secara turun-temurun.